Pembuatan Purwarupa Alat Ukur Konsentrasi CO2 Berbasis NodeMCU ESP8266 - Fitria Yudita; Nia Syafitri; Dwiria Wahyuni (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2023)
Carbon dioxide (CO2) is the largest contributor to greenhouse gas emissions, resulting in an increase in global temperatures. Unfortunately, this knowledge is not yet widely known among the general public. Therefore, providing information on daily CO2 levels can serve as a means to educate and raise awareness about the dangers associated with CO2 levels. To simplify access to CO2 concentration information, a prototype of a CO2 concentration measurement device based on the NodeMCU ESP8266 microcontroller, which can be connected to Wi-Fi, has been developed. To ensure data accuracy, the CO2 measurement device was calibrated using the NodeMCU ESP8266 microcontroller and data from an outdoor CO2 monitoring instrument at the BRIN (BPAA Pontianak) office, with an error value of 4.08%. The collected data from this device can be accessed through the Blynk application or a Google Sheets link. The test results demonstrate that the device can provide CO2 concentration levels with higher readings in areas characterized by high vehicle traffic, smoking, combustion activities, or a crowd of people.